Critical Dimensions of the ‘Legal Culture’ Approach: The Case of Classical Eurasianism and Eurasia’s Legal Union - Nazmutdinov, Bulat (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
This paper refers to the accurate usage of the word “Eurasian”, which is tightly connected with Russian Eurasianism, an intellectual movement that existed in the Interwar period, in the years 1921–1939. Nowadays, the concept of “Legal Culture” is rendered banal by comparative legal thinkers, who reduce it to legal tradition or even the legal system as a social system. In contrast to these theories, the Eurasianist jural project was mostly culture-oriented. For instance, the Eurasianist idea of Language Union, provided by Nikolai Trubetzkoy and the famous linguist Roman Jakobson, could be useful for developing a new concept of Legal Union instead of the idea of legal family. Piotr Savitzky’s notion of “Mestorazvitie”, Jakobson’s “method of linking”, and Nickolai Alekseev’s idea of “Right-Duty” could be very fruitful concepts for establishing cultural jurisprudence.